KLE CHANCELLOR PROUD OF PIONEER BATCH OF MEDICAL GRADUATES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
BELGAUM, INDIA, 23 June 2015 – The USMKLE Medical Programme is hoped to bring a sense of pride to India and Malaysia in providing yet another alternative for studies in higher education in the field of Medical Sciences.